Unleashing the industrial transformative capacity of innovations - Fontes, M.; Bento, N.; Andersen, A. D. (Environmental Innovation and Societal Transitions, 2021)
This paper investigates the conditions in which the development of new technologies induce structural change in the economy. A literature review reveals three factors that influence the industrial transformative capacity of a technology: context; complementarities; competition. We explore the dynamics of these factors, focusing on the extent and nature of induced activities in adjacent sectors. We apply this framework to study marine renewable energy technologies (MRET) in Portugal. Adjacent sector firms active in several MRET exhibited diversified activity, innovation and internal change. Comparing with Norway, where an offshore sector (oil & gas) supports the emergence of offshore wind, the absence of such sector in Portugal raises challenges but also creates opportunities for the transformation of several other sectors. We develop a new indicator to identify and compare the industrial transformative capacity of innovations. Finally, we discuss the extent to which context, complementarities and competition contribute to accelerate or hinder transformative change.